Sail away with me - Fox, Susan, 1952 July 31- (Fox, Susan, 1952 July 31- Blue Moon Harbor., 2018)
Bookseller Iris Yakimura grew up on Destiny Island and it<U+2019>s the only place where her painful shyness doesn<U+2019>t cripple her. An avid romance reader, she believes that one day the right man will come along<U+2014>one who loves her just the way she is. She never imagines that man will arrive in time for the holidays, like a gift. Or that he<U+2019>ll be a celebrity musician with a bad boy vibe<U+2014>and a warm heart . . . Julian Blake spent most of his teens on Destiny Island, before fleeing a mentor turned abuser. Music saved him. He has avoided the island, but now his injured father needs him. Plagued by unsettling memories, Julian<U+2019>s solace comes from surprising places<U+2014>and from smart, stunning Iris. When he feels compelled to expose his abuser, will Iris find the courage to stand by his side in the spotlight that will ensue<U+2014>much less embrace a love that might take her far from home? . . .